Longitudinal changes in symptom‐based female and male LUTS clusters. Issue 1 (25th November 2019) - Amundsen, Cindy L.; Helmuth, Margaret E.; Smith, Abigail R.; DeLancey, John O.L.; Bradley, Catherine S.; Flynn, Kathryn E.; Kenton, Kimberly S.; Henry Lai, H.; Cella, David; Griffith, James W.; Andreev, Victor P.; Eric Jelovsek, J.; et al.
Abstract: Aims: Lower urinary tract symptoms (LUTS) are diverse in type and variable in severity. We examined symptom change within the Symptoms of the Lower Urinary Tract Dysfunction Research Network (LURN) Observational Cohort study identified clusters over time and tested associations with treatments received. Methods: Patient‐reported LUTS and treatment data were collected at multiple time points between baseline and 12 months from the LURN Observational Cohort study. LUTS severity scores were calculated to summarize changes in symptom reporting over time in previously identified LURN clusters. Repeated measures linear regression models tested adjusted associations between cluster membership and severity scores. Results: Four‐hundred seventeen men and 396 women were classified into improved, unchanged, and worsened symptoms between baseline and 12 months (men: 44.1%, 40.5%, and 15.3%; women: 55.8%, 33.1%, 11.1%, respectively). Improvement in LUTS severity scores varied by cluster (estimated adjusted mean change from baseline range: −.04 change in standard deviations of severity scores (ΔSD) to −.67 ΔSD). Prostate surgery was associated with improved severity scores (−.63 ΔSD) in men, while stress incontinence surgery was associated with improved severity scores (−.88 ΔSD) in women. Conclusion: Symptom improvement varied by cluster indicating response to therapy differs amongst subtypes of patients with LUTS. The differential improvement of patients in clusters suggests mechanistic differences between clusters and may aid in selecting more targeted treatments in the future.